The Integration of Islam with the Local Culture of Tanete Kingdom (a Cultural Approach to the Historical Study) - Mundzir, Chaerul; Arif, Muhammad; Syatar, Abdul (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2021)
Tanete is one of the Bugis Kingdoms in South Sulawesi which has been established since the 16th century. This paper aims to explain the influence of Islamization on the socio-cultural life of the Tanete Kingdom in the 17th – 18th centuries. The process of Islamization which was started by King Tanete IX, named Petta Sugie, had an impact on two things, first, Islam was integrated in the elements of government with the existence of a saraq institution led by a Kalie. Second, the process of Islamization has an impact on initiation ceremonies or rites de passage. The changes were marked by the addition of Islamic elements and values in the birth-marriage-funeral rites